Implementation of Good Corporate Governance in the Financial Management System: JEL Classification: G34, H83, H61, D73, M48 - Ilham Z. Salle; Winarti Winarti; Ariyanti Inayah; Marsela Ria; Nur Alimin Azis (Newinera Publisher, 2026)
This study aims to determine the implementation of good corporate goernance in the financial management system of the Makale Selatan Dirict Office, Tana Toraja Regency. This study uses qualitative descriptive analysis. Data in this study were collected through observation, direct iter views and documentation. The results of this study indicate that the Makale Selatan District Government, Tana Toraja Regency has imple mented the principles of good corporate governance as in the Minister of Home Affairs Regulation Number 77 of 2020 which consists of transparecy, accountability, public participation, and efficiency in financial management in the Makale Selatan District, Tana Toraja Regency, although the implementation has not been optimal as in the principle of transparency because the Makale Selatan District Office, Tana Toraja Regency should create and manage an official website as a public information media. So that the public or other parties can more easily access information and the principle of transparency in financial management can be applied optimally, where the use of the website also shows that the sub-district follows technological developments and realizes modern and accountable governance.